Microstructure-mechanical properties relationships in vibration welded glass-fiber-reinforced polyamide 66: A high-resolution X-ray microtomography study. (May 2020) - Mofakhami, Eeva; Tencé-Girault, Sylvie; Perrin, Jonathan; Scheel, Mario; Gervat, Laurent; Ovalle, Cristian; Laiarinandrasana, Lucien; Fayolle, Bruno; Miquelard-Garnier, Guillaume
Abstract: The effect of initial fiber orientation and welding conditions on the mechanical properties and microstructure of 30 wt% glass-fiber-reinforced polyamide 66 was systematically evaluated. For all conditions studied no significant change in the polymer matrix was evidenced. However, fibers in the welded zone were reoriented toward the squeeze and vibration flows and this reorientation is related to the appearance of cavities, as evidenced by high-resolution synchrotron-based X-ray microtomography. It is shown that stress at break values of the welded samples increase with the thickness of the weld zone together with the minimum value of the fiber orientation tensor component in the tensile direction. A drop of strain at break is also related to an increase in the fibers' concentration in the weld. The maximum void volume fraction being measured on samples which have the thickest welded zones, counterintuitively it does not induce lower stress at break. Highlights: High-resolution X-ray microtomography of welded thermoplastic composites. Quantitative analysis of fiber reorientation and voids appearance in the weld zone. No influence of welding on the polymer crystallinity. Stress at break related to fiber orientation and weld zone thickness. Strain at break related to volumic fraction of fibers in the weld.